"It's too political": The overt and covert silencing of critical Latino/a voices. Issue 4 (November 2017) - Call-Cummings, Meagan
Abstract The concept of school-sponsored silencing of students in K-12 contexts in the United States is well documented, particularly in relation to students of color. Discussions have addressed and called into question implicit and explicit administrative and pedagogical practices of silencing that curb critical reflection and thinking. The case explored here explores both overt and covert practices of silencing as lived by Latino/a high school students in rural Idaho. By directing attention to silencing in this context, I argue that it can be much more routinely and unknowingly used than we might imagine, and that it has the potential to severely stymie critical conversations of change and eventually disempower in subtle ways.